A Quantitative Study on Leadership and Gen Z's Job Satisfaction: Its Impact on Employee Retention in The Private Sector in Indonesia - Guslina, Indri; Rinzani, Angga; Mantong, Joni; Moeins, Anoesyirwan; Rakhmat Kabul, Eka (International Journal of Accounting and Economics Studies, 2025)
People born between 1997 and 2012, known as Generation Z, are increasingly dominating the workforce. As private sector companies, particularly in Indonesia, face challenges in retaining this new generation of workers, it is becoming more critical to understand the factors that influence their job satisfaction and retention. Given Gen Z's unique expectations shaped by their familiarity with technology, desire for purpose-driven work, and demand for work-life balance private sector organizations must adopt tailored strategies to engage and retain them effectively. Customizing approaches that address these needs will play a crucial role in luring and keeping Gen Z employees in the private industry. The objectives of this study are to identify the main factors influencing job satisfaction among Gen Z workers in Indonesia's private sector and to investigate the relationship between job satisfaction and employee retention. The study aims to analyze how Gen Z's job satisfaction and their intentions to leave are correlated with company culture, management practices, employee recognition, and the integration of technology within private sector organizations. Data from Gen Z workers in private sector companies in Indonesia were collected using questionnaires as part of a quantitative research approach. The survey assessed various aspects of job satisfaction, including managerial support, career development opportunities, organizational culture, and the use of technology in the workplace. The data were analyzed using structural equation modeling (SEM) to examine the correlations between these factors, and the direct effects on employee retention were evaluated through regression analysis. According to the survey, job satisfaction among Gen Z workers in Indonesia's private sector is significantly influenced by management support, career development opportunities, and organizational culture. Additionally, Gen Z workers highly value the digital environments and technology tools that enhance their productivity. The study found that the relationship between management practices and employee retention is mediated by job satisfaction, indicating that improving job satisfaction can help reduce turnover in this group. The findings highlight the importance of adapting management practices to meet the unique needs of Gen Z workers in Indonesia's private sector. Private sector organizations should focus on fostering a supportive and inclusive work environment, providing clear career advancement opportunities, and leveraging technology to enhance the workplace. By improving job satisfaction, these companies can effectively increase employee retention rates and ensure a more engaged and productive workforce.
Keywords: Generation Z, Leadership, Job Satisfaction, Employee Retention, Private Sector, Indonesia